Humility Education for Santri Through Learning "Kitab Akhlakul Banin" at Islamic Boarding Schools - Rahmatullah, Azam Syukur (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
This research observes, explores, and discovers how Islamic boarding schools educate and teach the science of humility (tawadlu') to their santri (students). Through this research, the researcher also digs deeper into wasilah, or the tools used to educate and teach humility to the santri. This research approach was descriptive-analytical, in which it did not only look at the processes involved in Islamic boarding schools and analyzed more deeply, resulting in positive findings beneficial to the academic world. The research location was at the Al-Kamal Tambaksari Islamic Boarding School, Kuwarasan, Kebumen, with the primary informants being the Board of Directors of the Islamic Boarding School, the Head of the Madrasah Diniyah, the Deputy Head of the Kesantrian Curriculum, and the ustadz (teacher) of the teaching division at the Islamic Boarding School. The study results revealed that, first, the habituation of the humility teachings originates from the "Kitab Akhlakul Banin," which is a book about how to have positive morals and ethics, and the book also guides santri to have healthy personalities. Second, the teachings of the "Kitab Akhlakul Banin" are not only at the conceptual level but have also reached the applicative level, i.e., the santri have traditionally taught the humility teachings in their daily lives based on the book. Third, with the strengthening of exemplary in the humility aspect, all stakeholders always exemplify the humility teachings to the santri, not only the kyai but the leaders also exemplify it.